2012
DOI: 10.1159/000341811
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Extracorporeal Photopheresis

Abstract: Extracorporeal photopheresis (ECP) is a combination of leukapheresis and photodynamic therapy in which blood is treated with photoactivable drugs which are then activated with ultraviolet light and re-infused to the patient. It has been used successfully for more than 30 years in the treatment of erythrodermic cutaneous T-cell lymphoma (CTCL) and over 20 years for chronic graft-versus-host disease (GVHD). ECP has also shown promising results in the treatment of acute GVHD and other T-cellmediated diseases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
9
0
2
Order By: Relevance
“…ECP combines leukapheresis and photodynamic therapy, and can be performed using a multi‐step procedure or using a fully integrated system . The mechanism of photopheresis is not fully understood, however, it is theorized that T‐lymphocyte cells damaged by ultraviolet A (UVA) during the procedure activate the patient's immune system …”
Section: Introductionmentioning
confidence: 99%
“…ECP combines leukapheresis and photodynamic therapy, and can be performed using a multi‐step procedure or using a fully integrated system . The mechanism of photopheresis is not fully understood, however, it is theorized that T‐lymphocyte cells damaged by ultraviolet A (UVA) during the procedure activate the patient's immune system …”
Section: Introductionmentioning
confidence: 99%
“…The bestcharacterized subtypes of Tregs are those expressing CD4 and CD25 [149,150] . It is also suggested that ECP induces IL10 producing regulatory B cells, regulatory CD8 + T cells and IL10 producing Tregs Type 1 [167,169,170] . IL10, also known as cytokinesynthesis inhibitory factor, is a potent anti-inflammatory cytokine [171] .…”
Section: Extracorporealphotopheresismentioning
confidence: 99%
“…UVA ile ışınlanmış hücreler tekrar hastaya verilir 59 . UVA, lenfositlerde DNA hasarına yol açarak zararlı T-lenfositlerinin hasarlanmasını sağlar 60 . Dermatolojide evre 2-4 kutanöz T hücreli lenfoma tedavisinde 30 yıldır, kronik graft versus host hastalığı tedavisinde 20 yıldır kullanılmaktadır 59 .…”
Section: Azatiyoprinunclassified
“…Dermatolojide evre 2-4 kutanöz T hücreli lenfoma tedavisinde 30 yıldır, kronik graft versus host hastalığı tedavisinde 20 yıldır kullanılmaktadır 59 . Akut graft versus host hastalığı, Crohn hastalığı, sistemik skleroz gibi kollajen doku hastalıkları ve otoimmun büllü hastalıklarda da başarıyla kullanıldığını bildiren yayınlar mevcuttur 60 . Etkili ve yan etkiler açısından güvenli bir tedavi seçeneği olan ekstrakorporeal fotoferezin kullanımını sınırlayan en önemli engel, yüksek maliyetidir.…”
Section: Azatiyoprinunclassified